The Development of Antioxidant Nutraceuticals containing Chrysanthemum indicum L. Gummy Candy - Rahmasari, Firdaus Salvia; Sahid, Muhammad Novrizal Abdi; Siswanti, Dwi Umi; Darsih, Cici; Utami, Indrawati Dian; Alam, Lucky Prabowo Miftachul; Laksitorini, Marlyn Dian (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Chrysanthemum flowers (Chrysanthemum indicum L.) have been shown to contain flavonoid compounds and exert antioxidant activity. This brings Chrysanthemum indicum potential to be developed as a nutraceutical product. This study aims to evaluate the antioxidant activity of Chrysanthemum flowers before and after the formulation of Chrysanthemum indicum flower extract as a gummy candy. Gummy candy formulas were developed using variations of gelatin and pectin as gelling agents. In this study, Chrysanthemum flower extract was formulated into gummy candy. The physical characteristics evaluated include organoleptic tests, weight uniformity, elasticity, and moisture content. Optimization was performed using the simplex lattice design (SLD) method with the aid of the Design Expert software Ver. 13. The antioxidant activity of the chrysanthemum flower extract and gummy candy extract was evaluated using the DPPH radical scavenging method. Ascorbic acid was used as a positive control. The optimum formula for preparing the gummy candy was 11.51% of gelatin and 1.24% of pectin. The evaluation of weight uniformity, elasticity, and moisture content suggested that there is no significant difference between the optimum formula and the predicted value. Both the chrysanthemum flower extract and chrysanthemum flower gummy candy had strong antioxidant activity. The IC50 value of the extract was 67.80 ± 2.37 mg/mL while the gummy candy IC50 value was 82.93 ± 2.55 mg/mL. The antioxidant activity of Chrysanthemum indicum was slightly decreased after being formulated into gummy candy. These studies suggested that scientists are expected to anticipate the decrease of Chrysanthemum antioxidant activity in the gummy manufacturing process.